Determinants of non-accessibility to primary health care in the Ikela Health Zone, Ikela, Democratic Republic of the Congo - Botuli, Louison Lofoka; Mukandu, Basua Babintu; Eloko, Gerard Eya Matangelo; Mawunu, Monizi; Koto-Te-Nyiwa Ngbolua, Jean-Paul (Orapuh Journal, 2025)
Introduction Accessibility to healthcare in the Ikela Health Zone is a significant public health issue. The inability of households to access primary healthcare services hinders efforts to improve health outcomes. Addressing these barriers is essential for the development of a robust healthcare system. This study aims to identify the determinants of non-accessibility to primary healthcare in the Ikela Health Zone and to describe the various health services provided by healthcare institutions. Purpose The purpose of this study is to identify the factors that prevent households in the Ikela Health Zone from accessing primary healthcare services. Additionally, it aims to present an overview of the healthcare services available to the population within this area. Methods This study follows a descriptive, cross-sectional design and was conducted in the Ikela Health Zone between January 1 and September 30, 2024. The sample consisted of 50 heads of households, selected through a structured interview process. Data were collected using direct structured interviews, which allowed for the efficient gathering of relevant information. Results The findings revealed that overbilling for health services (40%) and the availability of curative care services (54%) are the primary factors affecting household accessibility to healthcare in the Ikela Health Zone. Additionally, curative care was identified as the most commonly offered health service in the region. These findings highlight critical barriers to healthcare access in the area. Conclusion The involvement of local health authorities, as well as national and international partners, is crucial to improving access to primary healthcare for households in the Ikela Health Zone. The perceived benefits of using primary care services showed minimal effects, with most categories having odds ratios close to 1, except for category 2, which had a negative relationship with an odds ratio of 0.207. The risk associated with the non-use of healthcare services was largely insignificant, with most categories showing either no effect or very low odds ratios. However, the availability of services in healthcare facilities was found to have a significant impact, particularly for category 2, where the odds ratio was 0.782, suggesting that improving the quality and availability of services in health facilities could reduce barriers to healthcare access.